Minyak Kenanga (Canangium odoratum Baill) Sebagai Repellent Lalat Rumah (Musca domestica) - Wijayanti Ratna Sari; Muryoto Muryoto; Abdul Hadi Kadarusno (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
Flies are vectors of some diseases such as dysentery, cholera, typhoid, diarrhea and worm in-fection. Various techniques of fly control can be applied, one of which is by using chemical sub-stances as repellent. Cananga (Canangium odoratum Baill) has the ability to repel flies be-cause contains phenolic compound, i.e. linalool, eugenol and geraniol, which basically can ex-pel insects. The purpose of this research was to determine the influence of various concentra-tion of cananga oil towards houseflies (Musca domestica) by measuring the power and duration of the obtained repellent. This research was an experiment with post-test only with control group design. The research objects, i.e. 625 houseflies, were used for five expeiment groups which consisted of three treatment groups and two control groups in five repetitions. One way anova test at ? 0.05 revealed that the repellent powers showed from the 20 %, 30 % and 40 % cananga concentration, and the positive control (camphor) and the negative control (castor oil) were significantly different. Therefore, it can be concluded that cananga oil concentration do in-fluence the repellent power. However, the effect on the duration was not significant. To con-clude, 40 % concentration (40 ml cananga oil in 60 ml castor oil) is the most effective for repel-ling houseflies. It has 34.4 % repellent power and 8,4 hours duration.